The Influence Of Profitability, Firm Size, Debt Policy And Ownership Structure On Investment Decisions With Growth Opportunity As A Moderating - Iryanto, Nadya Adella; Abdurrahman, Abdurrahman (Syntax Corporation, 2025)
This study aims to analyze the effect of profitability, firm size, debt policy, and ownership structure on investment decisions in oil and gas sector companies in Indonesia, with growth opportunity as a moderating variable. A quantitative approach is used in this study with secondary data from the financial statements of 19 companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023, as well as one additional company, Pertamina. The analysis method used is Generalized Least Square (GLS) and Moderated Regression Analysis (MRA) with the help of EViews 13 software and the research model used is the Fixed Effect Model. The results of the study show that simultaneously the four independent variables have a significant effect on investment decisions. Partially, profitability and ownership structure have a significant positive effect on investment decisions, debt policy has negatife effect on investment decisions while firm size does not have a significant effect. Growth opportunity has been proven to be unable to play its role as a moderating variable because it has not been able to weaken or strengthen the influence of profitability and debt policy on investment decisions. These findings provide important implications for companies in considering internal factors and growth opportunities when determining investment strategies amid global uncertainty.